ORANG KALANG DAN BUDAYANYA: TINJAUAN HISTORIS MASYARAKAT KALANG DI KABUPATEN KENDAL - Muslichin, Muslichin (History Department, Semarang State University and Historian Society of Indonesia, 2011)
This paper aims to explore and explain the history of Kalangse community in Kendal Regency. In the past, Kalang people occupied a minority position in the history. As time passes, they can show the real social position. History of the Kalang contained in the Village District Poncorejo Gemuh Kendal District at least give a concrete picture of how the development of cultural existence of these groups to influence the changing times.Ã‚Â What happens in Poncorejo provide a portrait of community life, especially community that occupy other coastal areas in Kendal regency.Ã‚Â Kalang people who in the Hindu-Buddhist kingdom do not get social status equal with other ethnic groups because of different cultural backgrounds or are considered untouchable, are recognized bt the Dutch colonial as more special because of the ethos and work performance in accordance with the spirit of colonial development.Ã‚Â The dark and boring history of communist life, finally becomes normal due to the effort of the policy of Dutch Colonial which recognized the equality of basic right for them, spreading of Islam, and the influence of modernization and globalization in this periode. Ã‚Â Key words: Kalangese, Culture, and Religion Ã‚Â Makalah ini bertujuan untuk mengeksplorasi dan menjelaskan sejarah masyarakat Kalang di Kabupaten Kendal. Di masa lalu, orang Kalang menempati posisi minoritas dalam sejarah. Dengan berjalannya waktu, mereka dapat menunjukkan posisi sosial yang nyata. Sejarah Kalang terutama di Desa Gemuh Kendal Poncorejo setidaknya memberikan gambaran konkret bagaimana perkembangan keberadaan budaya dari kelompok-kelompok itu untuk mempengaruhi perubahan zaman. Apa yang terjadi di Poncorejo memberi potret kehidupan masyarakat, terutama yang menempati daerah pesisir lainnya di Kabupaten Kendal sendiri. Orang Kalang pada masa Hindu-Buddha tidak mendapatkan status sosial yang sepadan dengan kelompok etnis lain karena latar belakang budaya yang berbeda atau dianggap tak tersentuh, bahkan selama pengakuan kolonial Belanda lebih istimewa karena etos dan kinerja bekerja sesuai dengan semangat pembangunan kolonial. Sejarah kehidupan masyarakat yang gelap dan membosankan, akhirnya menjadi normal karena upaya dari kebijakan kolonial Belanda yang mengakui kesetaraan hak dasar bagi mereka, menyebarkan Islam, dan pengaruh modernisasi dan globalisasi dalam periode ini. Kata kunci: Orang Kalang, Budaya, dan Agama Ã‚Â